Pandemic Kinship Families, Intervention, and Social Change in Botswana's Time of AIDS - Reece, Koreen M. (Social Sciences, 2022)
Shaped around the stories of one extended family, their friends, neighbours and community, this offers an intimate portrait of everyday life in Botswana's time of AIDS. It tackles questions relevant to scholars and practitioners of anthropology, public health, social work, and development. This title is available Open Access on Cambridge Core.